Testing of platelet function and application of rotary thromboelastometry in order to rationalize chemotherapy during myocardial revascularization and surgical treatment of heart valves - Vuković, Danijela; Živković, Tanja; Todorović, Milena; Čalija, Branko; Vuković, Petar; Balint, Bela (Medical Word, 2021)
Using intraoperative salvage of blood/erythrocytes (ISB/E) in the practice, rationalized application of allogeneic blood products and hemostatic-active drugs - based on “point-of-care” (POC) monitoring findings - it is possible to improve diagnosis and evaluate of transfusion hazards and increase efficacy of therapy of patients with excessive bleedings, with reduction of perioperative morbidity and mortality in cardiac surgery.This study was performed as a prospective analysis of platelet function using “multiple platelet function analyzer” (MEA; by Multiplate) system and examination of hemostasis by rotational thromboelastometry (ROTEM) during and immediately following myocardial revascularization and surgical treatment of valves in the Institute of Cardiovascular Diseases “Dedinje” for six years period for therapy of 1021 random selected patients.The study aim was to evaluate the influence of ISB/E and hemostatic drugs – indicated based on the results of platelet count and function (Multiplate) and hemostasis monitoring (ROTEM) in compared to allogeneic transfusions – on the incidence of bleedings, treatment efficiency and overall clinical outcome.In the perioperative period, a total of 617 (60.4%) patients were treated with ISB/E reinfusion only. Other patients (404; 39.6%) received allogeneic blood components too. Total 391 of them (38.3%) were treated (together by ISB/E) with transfusion of one to three units of allogeneic red blood cells (RBCs). There were only 13 (1.3%) polytransfunded (typically 10 - 15 units) patients. The rate of cardio-surgical reinterventions due to bleeding was only 2.5%.In conclusion, the application of the ISB/E strategy represents an effective and safe (reduced immune-mediated complications and risk of disease transmission) therapeutic approach. By monitoring MEA/ROTEM and implementation the algorithm of current transfusion therapy, it is possible to reduce significantly of allogeneic blood component therapy. The use of allogeneic RBCs is justified only when the possibilities of autologous transfusion and pharmacological hemostatic therapy have been exhausted.
Keywords: bleeding, blood components, cardio-surgery, Multiplate, ROTEM